Localization of heat shock protein HSPA6 (HSP70B') to sites of transcription in cultured differentiated human neuronal cells following thermal stress. (2nd December 2014) - Khalouei, Sam; Chow, Ari M.; Brown, Ian R.
Abstract Heat shock proteins (Hsps) are a set of highly conserved proteins that are involved in cellular repair and protective mechanisms. In order to identify potential stress‐sensitive sites in differentiated SH‐SY5Y human neuronal cells, localization of two inducible members of the HSPA (HSP70) family was investigated, namely HSPA6 (HSP70B') and HSPA1A (HSP70‐1). Following heat shock, yellow fluorescent protein (YFP)‐tagged HSPA6 and HSPA1A proteins localized to nuclear speckles that are enriched in RNA splicing factors (identified by SC35 and SON marker proteins) and then to the granular component of the nucleolus (identified by nucleophosmin). Subsequently, YFP‐HSPA6 protein, but not YFP‐HSPA1A, localized to the periphery of nuclear speckles that are sites of RNA transcription. The HSPA6 gene is present in the human genome but not in genomes of rat and mouse. Hence, current animal models of neurodegenerative diseases are lacking a potentially protective member of the HSPA family. <boxed-text content-type="graphic" id="jnc12970-blkfxd-0101" position="anchor" orientation="portrait"> </boxed-text> Potential stress‐sensitive sites were identified in differentiated human SH‐SY5Y cells by the localization of HSPA6 (HSP70B') and HSPA1A (HSP70‐1) to nuclear components following heat shock. HSPA6 and HSPA1A rapidly moved to nuclear speckles, enriched in RNA splicing factors, then to the granular layer of the nucleolus. Subsequently, HSPA6 exhibited a novel localization not observed for the more widely studied HSPA1A, namely association with the periphery of nuclear speckles that are sites of transcription. HS = heat shock; HSPA6 = HSP70B' protein; HSPA1A = HSP70‐1 protein.